OHSU 3D Printed CRISIS Ventilator - Albert Chi; Whitney Menzel; Evan Fontaine; Dennis Child; Stephanie Nonas (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
In response to national and international shortages in the availability of medical ventilators, our team has developed and tested a novel low-cost (~10 USD) 3D-printed flow-driven pressure-regulated mechanical ventilator capable of basic and complex ventilation needs. This device requires no electronics and can be sustained with either O2 tanks or standard hospital 50psi O2 wall supply. The design can be printed rapidly, mass-produced and immediately deliverable to any crisis areas in need. The CRISIS Ventilator has the potential to be produced on site depending on 3D printing capabilities. Our team includes physicians, scientists, a respiratory therapist, and engineers in healthcare dedicated to developing a rapidly deliverable ventilator solution to the global COVID-19 pandemic.